Social Responsibility Networks (SRN): The Role of the International Civil Society in Redressing the Negative Effects of Globalization at the Local Level (2019)
There is both theoretical and empirical evidence which indicates that the processes of globalization have intensified the onset of social exclusion and environmental problems. Globalized processes may also exacerbate inequalities that, in order to be readdressed, require transnational, transparent, accountable and participative governance systems, with an active and recognised contribution by the local community in the amelioration of these problems. This paper focuses on transnational participation of civil society actors as well as private corporations and state agencies, which together provide a platform for the development of a broader scope for corporate social responsibility (CSR).